A Proposal to Uniquely Distinguish Established Clade Names under the PhyloCode - Vlachos, Evangelos (2025)
The first edition of the PhyloCode recommends that established clade names should be italicized to distinguish them from vernacular names. To distinguish names established under the PhyloCode from names governed by the rank-based codes, the recommendations provide two examples, one involving the use of bracketed letters, the other involving the designation “clade” or the name of a rank. Italicization of all scientific names creates a conflict with the Zoological Code, while the use of bracketed letters or designations adds unnecessary complexity in print. To distinguish established clade names simultaneously from both vernacular names and scientific names governed by rank-based codes, I propose that established clade names be underlined. This is a simple solution that can be applied easily, it would make established clade names immediately recognizable, and it has some continuity with past and modern practices.